Hubungan Simbiotik Manusia Dengan Lingkungan Dalam Islam - Nawawi (HUMANISTIKA : Jurnal Keislaman, 2020)
This paper states that Islam is a comprehensive religion that not only regulates the problem of worship but covers all aspects of life and is not only related to thirst but also relates to spirituality. Islam has two important meanings for humans as a basic concept for life, namely the meaning of what religion does (the function of religion in life) and the meaning of wahat is religion (the meaning of religion for life). Both of these meanings are closely related to human relations with the environment, where the relationship of both are equal or symbiotic, namely mutual benefit between humans and the environment. As a form of implementation of rahmatal lil 'alamin, human relations with the environment consists of three principles. First, the principle of respect for nature. Second, the principle of environmental responsibility. Third, the principle of caring for the environment. These three principles will not be effective, so it requires control from the authorities, namely severe punishment to the death penalty. Without severe punishment, the environment will become extinct because it is exploited by humans arbitrarily.